- Thread starter
- Admin
- #1

I have posted a link there to this topic so the OP can see my work.Solve the initial value problem x^2 y" + xy' - y = 0?

solve the initial value problem x^2 y" + xy' - y = 0 with initial conditions: y(1)= 0 & y'(1) = 2

- Thread starter MarkFL
- Start date

- Thread starter
- Admin
- #1

I have posted a link there to this topic so the OP can see my work.Solve the initial value problem x^2 y" + xy' - y = 0?

solve the initial value problem x^2 y" + xy' - y = 0 with initial conditions: y(1)= 0 & y'(1) = 2

- Thread starter
- Admin
- #2

Hello raqandre,

We are given the IVP:

\(\displaystyle x^2y"+xy'-y=0\) where \(\displaystyle y'(1)=2,\,y(1)=0\)

One way to proceed is the guess a solution of the form:

\(\displaystyle y=x^r\)

and so:

\(\displaystyle y'=rx^{r-1}\)

\(\displaystyle y''=r(r-1)x^{r-2}\)

Now, substituting into the ODE gives us:

\(\displaystyle x^2\left(r(r-1)x^{r-2} \right)+x\left(rx^{r-1} \right)-\left(x^r \right)=0\)

\(\displaystyle x^r\left(r(r-1)+r-1 \right)=0\)

\(\displaystyle x^r\left(r^2-1 \right)=0\)

\(\displaystyle x^r(r+1)(r-1)=0\)

Thus, the general solution is:

\(\displaystyle y(x)=c_1x+c_2x^{-1}\)

Differentiating, we find:

\(\displaystyle y'(x)=c_1-c_2x^{-2}\)

Using the initial conditions, we get the linear system:

\(\displaystyle y'(1)=c_1-c_2=2\)

\(\displaystyle y(1)=c_1+c_2=0\)

From which we may determine:

\(\displaystyle c_1=1,\,c_2=-1\)

Thus, the solution satisfying the given IVP is:

\(\displaystyle y(x)=x-x^{-1}=x-\frac{1}{x}\)

Thank you.Hello raqandre,

We are given the IVP:

\(\displaystyle x^2y"+xy'-y=0\) where \(\displaystyle y'(1)=2,\,y(1)=0\)

One way to proceed is the guess a solution of the form:

\(\displaystyle y=x^r\)

and so:

\(\displaystyle y'=rx^{r-1}\)

\(\displaystyle y''=r(r-1)x^{r-2}\)

Now, substituting into the ODE gives us:

\(\displaystyle x^2\left(r(r-1)x^{r-2} \right)+x\left(rx^{r-1} \right)-\left(x^r \right)=0\)

\(\displaystyle x^r\left(r(r-1)+r-1 \right)=0\)

\(\displaystyle x^r\left(r^2-1 \right)=0\)

\(\displaystyle x^r(r+1)(r-1)=0\)

Thus, the general solution is:

\(\displaystyle y(x)=c_1x+c_2x^{-1}\)

Differentiating, we find:

\(\displaystyle y'(x)=c_1-c_2x^{-2}\)

Using the initial conditions, we get the linear system:

\(\displaystyle y'(1)=c_1-c_2=2\)

\(\displaystyle y(1)=c_1+c_2=0\)

From which we may determine:

\(\displaystyle c_1=1,\,c_2=-1\)

Thus, the solution satisfying the given IVP is:

\(\displaystyle y(x)=x-x^{-1}=x-\frac{1}{x}\)

- Thread starter
- Admin
- #4